EXcess Idle Time - Bandi, Federico M.; Pirino, Davide; Renò, Roberto (Econometrica, 2017)
The gCube System - AquaMaps Species View Portlet ————————————————– Species view explorer portlet for AquaMaps suite This software is part of the gCube Framework (https://www.gcube-system.org/): an open-source software toolkit used for building and operating Hybrid Data Infrastructures enabling the dynamic deployment of Virtual Research Environments by favouring the realisation of reuse oriented policies. The projects leading to this software have received funding from a series of European Union programmes including: * the Sixth Framework Programme for Research and Technological Development - DILIGENT (grant no. 004260); * the Seventh Framework Programme for research, technological development and demonstration - D4Science (grant no. 212488), D4Science-II (grant no. 239019),ENVRI (grant no. 283465), EUBrazilOpenBio (grant no. 288754), iMarine (grant no. 283644); * the H2020 research and innovation programme - BlueBRIDGE (grant no. 675680), EGIEngage (grant no. 654142), ENVRIplus (grant no. 654182), Parthenos (grant no. 654119), SoBigData (grant no. 654024); Version ————————————————– 1.3.3-4.0.0-130288 (2016-11-27) Please see the file named "changelog.xml" in this directory for the release notes. Authors ————————————————– * Fabio Sinibaldi (fabio.sinibaldi-AT-isti.cnr.it) Istituto di Scienza e Tecnologie dell'Informazione "A. Faedo" - CNR, Pisa (Italy). Maintainers ———– * Fabio Sinibaldi (fabio.sinibaldi-AT-isti.cnr.it) Istituto di Scienza e Tecnologie dell'Informazione "A. Faedo" - CNR, Pisa (Italy). Download information ————————————————– Source code is available from SVN: http://svn.research-infrastructures.eu/public/d4science/gcube/trunk/portlets/user/aquamapsspeciesview Binaries can be downloaded from the gCube website: https://www.gcube-system.org/ Installation ————————————————– Installation documentation is available on-line in the gCube Wiki: https://wiki.gcube-system.org/gcube/index.php/AquaMaps_Suite Documentation ————————————————– Documentation is available on-line in the gCube Wiki: https://wiki.gcube-system.org/gcube/index.php/AquaMaps_Suite https://wiki.gcube-system.org/gcube/index.php/AquaMaps_Suite Support ————————————————– Bugs and support requests can be reported in the gCube issue tracking tool: https://support.d4science.org/projects/gcube/ Licensing ————————————————– This software is licensed under the terms you may find in the file named "LICENSE" in this directory.